Prevalence of anti‐Hepatitis E antibodies and impact on disease severity in non‐alcoholic fatty liver disease. Issue 1 (6th November 2020) - Paternostro, Rafael; Traussnigg, Stefan; Staufer, Katharina; Mandorfer, Mattias; Halilbasic, Emina; Lagler, Heimo; Stift, Judith; Wrba, Fritz; Munda, Petra; Trauner, Michael
Abstract : Aim: In most immune‐competent individuals, hepatitis E (HEV) infections appear silent. It is unclear whether past HEV infections deteriorate disease severity in patients with non‐alcoholic fatty liver disease (NAFLD). Methods: Patients with biopsy‐proven NAFLD and data on anti‐HEV immunoglobulin M (HEV‐IgM) and anti‐HEV IgG antibodies (HEV‐IgG) were included. The NAFLD activity score (NAS) was used to grade and stage all liver biopsy samples. The HEV‐IgG prevalence was compared to a healthy cohort of 997 subjects. Results: One hundred sixty‐seven patients with NAFLD were included with the following characteristics: age, 50 ± 13 years; NAS ≤4, 89 (53.3%); NAS 5–8, 78 (46.7%); cirrhosis, 16 (9.6%). Two patients (1.2%) were HEV‐IgM‐positive, however HEV polymerase chain reaction remained negative and no signs of acute hepatitis were seen. Forty‐four patients (26.3%) were HEV‐IgG‐positive and they were significantly older (55 ± 10 years vs. 48 ± 13 years, P  < 0.001) and predominantly men (31 [70.5%] vs.13 [29.5%], P  = 0.022). Distribution across NAS ( P  = 0.610) was not different. However, HEV‐IgG‐positive patients were significantly more often found with cirrhosis (8 [18.2%] vs. 8 [6.5%], P  = 0.024) and liver stiffness values >10 kPa (14 [58.2%] vs. 29 [43.3%], P  = 0.026). Multivariable analyses revealed age (odds ratio [OR], 1.054 [1.022–1.086]) and male sex (OR 2.77 [1.27–6.04]) associated with HEV‐IgG positivity. Presence of diabetes (OR 3.86 [1.18–12.59]), higher aspartate aminotransferase levels (OR, 1.02 [1.006–1.033]), and HEV‐IgG seropositivity (OR 3.52 [1.11–11.13]) were independently linked to cirrhosis. Finally, HEV‐IgG positivity was not independently associated with NAFLD patients in a case–control study including healthy subjects. Conclusions: Prevalence of anti‐HEV‐IgG antibodies in patients with NAFLD is linked to age and male sex. Furthermore, previous HEV infection was an independent risk factor for cirrhosis. Whether this finding is causal or solely associative is unclear and should be elucidated in future studies.